Studi Perbandingan Pandangan Yusuf al-Qaradawi dan Ibn Bāz tentang Penggunaan Tanah Wakaf Masjid untuk Lembaga Pendidikan - Muhammad Waliyuddin Yusuf; Ahmad Fajruddin Fatwa (Lembaga Yasin AlSys, 2026)
The utilization of mosque waqf land for the benefit of educational institutions is a contemporary fiqh issue that has given rise to differing views among scholars, amid the growing need of the Muslim community for educational facilities and the obligation to maintain the primary function of mosque waqf in accordance with the original intention of the donor. This study aims to analyze and compare the views of Yusuf al-Qaradawi and ʿAbd al-ʿAzīz ibn ʿAbd Allāh Ibn Bāz regarding the use of mosque waqf land for educational institutions, with particular emphasis on differences in their methods of legal istinbāṭ and the legal implications. This is a normative legal study employing library research and a qualitative-descriptive approach, using primary sources in the form of the works and fatwas of both scholars as well as relevant secondary sources. The findings indicate that Yusuf al-Qaradawi tends to permit the utilization of mosque waqf land for education as long as it does not eliminate the mosque’s primary function and remains in line with the objectives of waqf, grounded in the approach of maqāṣid al-sharīʿah and the principle of public interest (maṣlaḥah). In contrast, Ibn Bāz adopts a stricter and more textual position, stressing the obligation to preserve the allocation of waqf in accordance with the conditions set by the wāqif and rejecting any change in the function of waqf without clear evidentiary grounds. These divergent views reflect the dynamics of ijtihād in contemporary waqf fiqh and demonstrate that the issue of utilizing mosque waqf for education constitutes an ijtihādiyyah domain that remains open to scholarly disagreement, while still prioritizing prudence and the welfare of the Muslim community.